Effect of functionalized multi-walled carbon nanotubes on the microstructure and performances of PVDF membranes. Issue 93 (11th October 2015) - Yu, Zongxue; Zeng, Guangyong; Pan, Yang; Lv, Liang; Min, Hui; Zhang, Lei; He, Yi
<x xml:space="preserve">Abstract</x> Functionalized multi-walled carbon nanotubes (f-MWCNTs) were synthesized by grafting carboxyl groups and 3-aminopropyltriethoxysilane (APTS) on the nanotube surface, respectively.